Percutaneous Cholecystostomy: An Update on Current Management in Acute Cholecystitis - Rajah, Kumar Hari (Medical Research and Its Applications Vol. 11, 2024)
Percutaneous cholecystostomy is a minimally invasive procedure that is performed to treat high-risk and elderly patients who present with acute cholecystitis. It can be performed by the transhepatic or transperitoneal route. The tube is kept for a period of 21 days and a tube cholangiography is performed before removal. Percutaneous cholecystostomy is used as a bridging procedure to stabilize them and perform a cholecystectomy later. In this chapter, we look at the indication, outcomes and comparison with emergency cholecystectomy in the management of acute cholecystitis in high-risk and elderly patients.